Incidencia de la producción cacaotera en la economía familiar de la parroquia La Unión cantón Babahoyo - Valero Arriaga, Edgar Omar (2019)
SUMMARY The interview with cocoa producers showed a range of ages ranging from 29 to 85 years of age, with an average of 56 years, indicating that farmers engaged in cocoa activity have great experience in the work of this crop. According to the average age of 56 years of the respondents, is high compared to the ratio of 21 years of age that corresponds to the average population of the La Unión parish, which could be a factor that affects the production of cocoa in the area; Because this crop requires physical effort by the manual work that involves keeping the crop in good condition. In the results found, 80% of those interviewed have completed their basic education, which corresponds to primary, while 10% culminated in high school and the remaining 10% have studied at the university, but 0.1% ended the race University. Important Reasons Why the highest percentage of them are presented as farmers without a technical preparation, 20% perform day labor activities in the banana Plantation La Clementina and the remaining 30% are devoted to other activities such as the sale of products alcoholics or food; This reduces the time spent on cocoa cultivars, resulting in low yields; And by earning the basic salary in its non-agricultural activities it does not supply the household expenses in particular the food and basic services, where the total costs between health, education and those already mentioned amount to an average of 230 dollars per month; Big problem at the moment of investing in the phytosanitary and nutritional care of their cocoa crops. With yields average of 16.4 sacks per hectare, minimum to 1 sack/ha and maximum of 55 sacks per hectare; Always depending on the investment and management of the crop. As for the channel of marketing of Cocoa in the La Union parish The results found show how to operate the intermediaries, many of them make non-legal loans to the producers pawning their crops before being marketed.